SERUM GROWTH HORMONE CONCENTRATIONS AND RELATED FACTORS IN STUDENTS OF SEVERAL JUNIOR HIGH SCHOOLS IN THAI NGUYEN PROVINCE (Vietnam Journal of Community Medicine, 2026)
Background: Growth hormone (GH) is a crucial hormone affecting the physical development and metabolism of children, especially during puberty.Objective: To describe the current situation and factors associated with low serum GH levels in students of some junior high schools in Thai Nguyen province in 2025.Methods: A cross-sectional descriptive study was conducted on 179 junior high school students aged 10-14 years in 3 schools in Thai Nguyen City. Related factors included age, gender, BMI, central obesity (WHtR), and micronutrient deficiencies (calcium, iron, zinc, and vitamin D).Results: The prevalence of low serum GH was 16.2%. The 13-year-old group had a significantly lower risk of low GH than the other age groups (AOR = 0.28; 95% CI: 0.03-0.30; p = 0.003). Female students were 92% less likely to be at risk of low serum GH concentration than males (AOR = 0,08; 95%CI: 0,02-0,36; p < 0,001). Calcium deficiency increased the risk of low serum GH (AOR = 3,90; 95%CI: 1,02-14,86; p=0,046).Conclusion: The prevalence of low serum GH among students in Thai Nguyen City is quite high; overweight, obesity, and central obesity are factors associated with GH deficiency in junior high school students.
Keywords: Growth hormone, Growth hormone deficiency (GHD), junior high school students, Thai Nguyen.